Polycomb PHF19 binds H3K36me3 and recruits PRC2 and demethylase NO66 to embryonic stem cell genes during differentiation - Bracken, Adrian (My University, 2012)
Polycomb group proteins are repressive chromatin modifiers with essential roles in metazoan development, cellular differentiation and cell fate maintenance. How Polycomb proteins access active chromatin to confer transcriptional silencing during lineage transitions remains unclear. Here we show that the Polycomb repressive complex 2 (PRC2) component PHF19 binds trimethylated histone H3 Lys36 (H3K36me3), a mark of active chromatin, via its Tudor domain. PHF19 associates with the H3K36me3 demethylase NO66, and it is required to recruit the PRC2 complex and NO66 to stem cell genes during differentiation, leading to PRC2-mediated trimethylation of histone H3 Lys27 (H3K27), loss of H3K36me3 and transcriptional silencing. We propose a model whereby PHF19 functions during mouse embryonic stem cell differentiation to transiently bind the H3K36me3 mark via its Tudor domain, forming essential contact points that allow recruitment of PRC2 and H3K36me3 demethylase activity to active gene loci during their transition to a Polycomb-repressed state.
PUBLISHED
Keywords: Stem cells; Polycomb proteins; Cancer; Genes & Society